Economics and technical change - Hugh-Jones, E. M.; British Association for the Advancement of Science (Oxford ; B. Blackwell, 1969)
This contains the papers read to Section F (Economics) and some read jointly to Section F with Section G (Engineering) at the 1968 meeting of the British Association for the Advancement of Science. These papers examine the implications of technical change, innovation and technology. Papers include: impact of technical change; management and technology; economics of scale-generation of electrical power; economics of scale-computing systems; prospects of 1,000 passenger aircraft; trade unions and technical change among others.
"Papers presented to Section F (Economics) and jointly to Sections F and G (Engineering) at the 1968 Annual Meeting of the British Association for the Advancement of Science".
Includes bibliographical references and index.
lje 10/05/2018
Loans
Keywords: Technological innovations; Research, Industrial; Industries; Industrial relations